PERBANDINGAN PERPINDAHAN DAYA PADA MESIN PEMERAS KELAPA - Rahmadsyah, Rahmadsyah; Hasanah, Moraida; Bara, Aulia Akbar Batu; Sadun, Sadun; Fauzi, Mhd; Azhar, Muhammad (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract : This study aims to analyze and compare theoretical and actual power transfer in a coconut squeezer machine to determine the efficiency of the transmission system used. This coconut squeezer machine is designed using a 220 V electric motor with a rotational speed of 4500 rpm connected to a transmission system consisting of a pulley, a V-belt (type M33), and a gearbox with a reduction ratio of 1:30. This power transmission process results in a reduction in rotational speed from the motor to the screw press shaft, which functions to squeeze the coconuts into coconut milk. The research method used was theoretical computation based on the mechanical parameters of the transmission components and comparative analysis with actual test results. The calculation data included theoretical motor power, output power at the screw press shaft, torque, and transmission system efficiency. The calculation results showed that the theoretical motor power was 280 Watts, while the actual power at the screw press shaft was 239.4 Watts. A power loss of 40.6 watts, or approximately 14.5%, occurred due to V-belt inaccuracy, slippage, and mechanical losses in the gearbox. The total efficiency of the transmission system was 85.5%, indicating adequate mechanical performance. Based on the analysis, this coconut press machine is capable of operating well and stably for both household and industrial applications. Keywords: Power Transfer, EFFiciency, Coconut Press Machine, Mechanical Transmission, Gearbox, V-Belt, Electric Motor Abstrak : Penelitian ini bertujuan untuk menganalisis dan membandingkan peralihan daya teoritis dan daya aktual pada mesin pemeras kelapa, guna mengetahui tingkat efisiensi sistem transmisi yang digunakan. Mesin pemeras kelapa ini dirancang menggunakan motor listrik bertenaga 220 V dengan kecepatan putar 4500 rpm yang dihubungkan ke sistem transmisi berupa pulley, sabuk-V (V-belt tipe M33), dan gearbox dengan rasio reduksi 1:30. Proses transmisi daya ini menghasilkan penurunan putaran dari motor menuju poros ulir press yang berfungsi untuk memeras kelapa menjadi santan. Metode penelitian yang digunakan adalah komputasi teoritis berdasarkan parameter mekanik komponen transmisi serta analisis perbandingan dengan hasil pengujian aktual. Data perhitungan meliputi daya teoritis motor, daya keluaran pada poros ulir press, torsi, dan efisiensi sistem transmisi. Hasil perhitungan menunjukkan bahwa daya teoritis motor sebesar 280 Watt, sedangkan daya aktual pada poros ulir press sebesar 239,4 Watt. terjadi kehilangan daya sebesar 40,6 Watt atau sekitar 14,5% akibat akurasi pada V-belt, slip, serta rugi mekanis pada gearbox. Efisiensi total sistem transmisi diperoleh sebesar 85,5%, yang menunjukkan bahwa sistem mekanik bekerja cukup Berdasarkan hasil analisa, mesin pemeras kelapa ini mampu bekerja dengan baik dan stabil untuk skala rumah tangga maupun industri. Kata Kunci: Perpindahan Daya, Efisiensi, Mesin Pemeras Kelapa, Transmisi Mekanik, Gearbox, V – Belt, Motor Listrik.